The Genetic and Environmental Etiology of the Association between Vocabulary and Syntax in First Grade. Issue 2 (3rd April 2018) - Mimeau, Catherine; Dionne, Ginette; Feng, Bei; Brendgen, Mara; Vitaro, Frank; Tremblay, Richard E; Boivin, Michel
ABSTRACT: This twin study examined the genetic and environmental etiology of vocabulary, syntax, and their association in first graders. French-speaking same-sex twins ( n  = 555) completed two vocabulary tests, and two scores of syntax were calculated from their spontaneous speech at 7 years of age. Multivariate latent factor genetic analyses showed that lexical skills were influenced mainly by the environment shared between the twins, whereas syntactic skills were influenced exclusively by genes and unique environment. Moreover, the moderate association between vocabulary and syntax was mostly due to common genetic factors. These novel findings may be attributable to the use of latent factors and the population studied. More research is needed to determine the specific factors involved in lexical and syntactic skills at this developmental period.